A meta-analysis for assessing the contributions of trypsin and chymotrypsin as the two major endoproteases in protein hydrolysis in fish intestine - Solovyev, Mikhail M. (Comparative biochemistry and physiology. Part A: Molecular & integrative physiology)
For the majority of fish species, regardless of being gastric or agastric, trypsin and chymotrypsin are known as the two main alkaline proteases responsible for the initial stage of protein hydrolysis in the fish intestine. Although the critical role of these proteases for protein hydrolysis in fish intestine is without doubt, the relative input of each enzyme in protein hydrolysis is still unclear. Data used in the present study has been retrieved from a bibliographic search using the Dimensions application (https://app.dimensions.ai/discover/publication tool). Retrieved articles were carefully inspected to identify whether they contained the description of the development of ontogenetic activities for trypsin, chymotrypsin, and total alkaline proteases in fish intestine. From the list of consulted articles, 21 studies were chosen based on correlation coefficients (Pearson correlation test), and four groups of fish were identified with high significant correlation between 1) the activity of chymotrypsin and total alkaline proteases; 2) the activity of trypsin, chymotrypsin, and total alkaline proteases; 3) the activity of trypsin and total alkaline proteases, and 4) mainly negative correlation between trypsin, chymotrypsin, and total alkaline proteases. These results indicated that the relative inputs of trypsin and chymotrypsin in protein hy- drolysis may vary significantly among different fish species, which is a crucial point for proper understanding of species-specific digestive traits in both natural and aquaculture scenarios.